Perceptions towards MySejahtera, e-Penjana: Identifying key factors - Lee, Chien Sing *; Chua, Ser Jin; Kok, Ming Ho (The Institute of Electrical and Electronics Engineers, Inc., 2021)
Hybrid systems are increasingly popular to reduce complexity as well as to integrate the best of diverse options. This paper explores Malaysians’ perceptions towards the MySejahtera contact tracing app and e-Penjana, its accompanying e-wallet service provider. Findings highlight that mapping to the Capability Maturity Model and design thinking in MySejahtera-e-Penjana, has led to a needs-based government-citizen communication means and an open/scalable/extensible supply chain strategy. Analyses using logistic regression and clustering indicate that usefulness, ease of use and social norms are the most important in accepting MySejahtera, and for e-Penjana, convenience, variety and the types of incentives. Consequently, we gather requirements on a healthcare chatbot, to aid/educate the seniors, who may be less tech-savvy. We surmise, for the above apps, data mining can lead to context-aware help, and useful related product recommendations. With additional integration and smart partnerships, it is a testbed for interconnected extensions.